2023
DOI: 10.3390/molecules28217346
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-Guided Assessment of Antioxidative, Anti-Inflammatory and Antimicrobial Activities of Extracts from Medicinal Plants via High-Performance Thin-Layer Chromatography

Marko D. Jović,
Snezana Agatonovic-Kustrin,
Petar M. Ristivojević
et al.

Abstract: Natural products and their analogues have contributed significantly to treatment options, especially for anti-inflammatory and infectious diseases. Thus, the primary objective of this work was to compare the bioactivity profiles of selected medicinal plants that are historically used in folk medicine to treat inflammation and infections in the body. Chemical HPTLC fingerprinting was used to assess antioxidant, phenolic and flavonoid content, while bioassay-guided HPTLC was used to detect compounds with the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…The vast majority of the plant species used in this experiment are known, especially in pharmacy, as plants with medicinal properties and as ingredients of medicines recommended for respiratory diseases (e.g., Herbapect cough syrup) or as immunityboosting medicines (e.g., Sinupret), although the therapeutic substances were obtained from morphological parts other than flowers [56][57][58]. Most of the plants used in our experiments are also identified in the literature as potentially effective plants with a range of beneficial qualities, such as antibacterial, anti-inflammatory, antiviral, and antioxidative properties [31]. However, they have not been used as food additives, especially as flowers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of the plant species used in this experiment are known, especially in pharmacy, as plants with medicinal properties and as ingredients of medicines recommended for respiratory diseases (e.g., Herbapect cough syrup) or as immunityboosting medicines (e.g., Sinupret), although the therapeutic substances were obtained from morphological parts other than flowers [56][57][58]. Most of the plants used in our experiments are also identified in the literature as potentially effective plants with a range of beneficial qualities, such as antibacterial, anti-inflammatory, antiviral, and antioxidative properties [31]. However, they have not been used as food additives, especially as flowers.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, Ðor dević et al [59] demonstrated the most intense extraction of rutin and quercetin in an acacia honey sample enriched with 10% of the Sophora flower (150.24 mg/kg of rutin and 1338.93 mg/kg of quercetin), which moreover had a pleasant taste and aroma. In their study, Jović et al [31] demonstrated the high pro-health potential of nineteen extracts from the leaves and flowers of medicinal plants and herbs, including cowslip primrose (Primula veris L.) flower, black elderberry (Sambucus nigra L.) flower, and high mallow (Malva sylvestris L.) flower. Among these, the cowslip primrose (Primula veris L.) extract was characterised by the highest antioxidative potential of 188.5 GAE mg•g −1 , with black elderberry (Sambucus nigra L.) extract coming second with an antioxidative activity of 170.4 GAE mg•g −1 , while high mallow (Malva sylvestris L.) had a potential 10 times lower than black elderberry (Sambucus nigra L.) flowers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioautography was performed against five bacterial strains, encompassing both Gram-negative strains, E. coli ATCC 35218 and K. pneumoniae ATCC 29665, and Gram-positive strains, S. aureus ATCC 6538, MRSA ATCC 33591 and B. subtilis ATCC 6633 according to a modified procedure described in the literature. 39 The standard bacterial strains were cultivated on nutrient agar slants for 24 hours at 37 °C. Each well-grown culture was subsequently suspended in 5 mL of sterile physiological solution.…”
Section: Methodsmentioning
confidence: 99%
“…The time of the coronavirus pandemic, time of unceasing restrictions, limitations in contact has brought society closer to nature, or has simply restored the proper respect and importance that nature is due. In recent years numerous studies were undertaken based on traditional medicine, herbal medicine and biomedicine [47].…”
Section: Introductionmentioning
confidence: 99%